KEMAMPUAN MEMBACA MEMAHAMI TEKS DIALOG BAHASA MANDARIN SISWA KELAS XII SMA INSAN CENDEKIA SYECH YUSUF GOWA - Moch Ibnu Fiha Al Habsy; Burhanuddin Burhanuddin; Sukmawaty Sukmawaty (Universitas Negeri Makassar, 2020)
Abstract. The research was conducted to obtain data and information about the ability to read and understand Mandarin in Class XII SMA Insan Cendekia Syech Yusuf Gowa. This type of research uses quantitative descriptive. The population in this study were students of class XII SMA Insan Cendekia Syech Yusuf Gowa which consisted of 2 classes with a total of 47 students. Sampling using random sampling with a sample size of 1 class consisting of 22 students. The research data were obtained through a reading skills test to understand Mandarin. Data analysis using average and percentage search techniques with results that show sufficient (75.2%). Thus, this study shows that the ability to read and understand students of class XII SMA Insan Cendekia Syech Yusuf Gowa is sufficient (75.2%).